2021
DOI: 10.2147/jhc.s334935
|View full text |Cite
|
Sign up to set email alerts
|

Re-Recognizing the Cellular Origin of the Primary Epithelial Tumors of the Liver

Abstract: The primary epithelial tumors of the liver (PETL) are composed of a series of heterogeneous tumors. Although the classification of PETLs has been updated several times by the World Health Organization, the cellular origins of some tumors in this family remain to be precisely depicted. In addition, certain tumors in different categories have similar histology, molecular phenotypes and biological characteristics, suggesting that they may have the same cellular origin. In this work, a narrative review method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 101 publications
(218 reference statements)
0
5
0
Order By: Relevance
“…This finding illustrates that caution must be used when diagnosing a neuroendocrine component within an HB and the designation should be reserved for those cases in which both morphologic and immunophenotypic neuroendocrine features are present and not on focal expression of neuroendocrine markers alone. Interestingly, previous studies have demonstrated that subsets of hepatoblasts and the more primitive liver stem cells in the developing liver express neuroendocrine markers including NCAM and chromogranin [ 25 ]. We have also noted expression of synaptophysin within embryonal areas of HB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding illustrates that caution must be used when diagnosing a neuroendocrine component within an HB and the designation should be reserved for those cases in which both morphologic and immunophenotypic neuroendocrine features are present and not on focal expression of neuroendocrine markers alone. Interestingly, previous studies have demonstrated that subsets of hepatoblasts and the more primitive liver stem cells in the developing liver express neuroendocrine markers including NCAM and chromogranin [ 25 ]. We have also noted expression of synaptophysin within embryonal areas of HB.…”
Section: Discussionmentioning
confidence: 99%
“…We have also noted expression of synaptophysin within embryonal areas of HB. Synaptophysin and chromogranin are also expressed within the developing ductal plate, the site of the development of the intrahepatic bile ducts [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations